Comprehensive Review of Integrated Approaches to Cooperation and Collaboration in Emergency Response and Crisis Management - ALSAWIDAN, AYIDH HAMAD; AL SAMA, REEM ABDULLAH HUSSAIN; AL SAMA, ASHWAQ ABDULLAH HUSSAIN; ALSAAD, DAREEN MUBARAK SAEED; ALBAKHTAN, AMANI KHODEER SEED; ALQAHTANI, SARA HASSAN; MOAFA, AHOOD MOHAMMED Q; ALALHARETH, SALEH DHAFER SAEED; ALSAWIDAN, SAIF MUSLIH MOHAMMAD; AL-SUWAIDAN, HADI MUSLEH MOHAMMED (Journal of Ecohumanism, 2024)
There needs to be positive coordination and cooperation between governmental and non-governmental organizations, private businesses, and the population at large, especially during an emergency period. This paper will provide a detailed review of integrated approaches to crisis management, emphasizing the importance of establishing lines of communication and interdependency in crisis management. The review of the current topic focuses on identifying the various success and failure strategies of the recent worldwide crisis while stressing multilateral and interdisciplinary cooperation. Drawing from case studies and existing literature, this paper seeks to provide lessons learned for improving preparedness, response, and recovery during crises in the future.